Extended Inflammation Parameters (EIP) as Markers of Immune System Cell Activation in Psoriasis - Anna Kowalska-Kępczyńska; Mateusz Mleczko; Weronika Domerecka; Marcin Mazurek; Dorota Krasowska; Teresa Małecka-Massalska; Helena Donica (International Journal of Inflammation)
Psoriasis is an inflammatory, autoimmune disease that affects approximately 2% of the population. The inflammation in psoriasis can be systemic, so despite a predominantly cutaneous manifestation, it also affects the internal organs. The diagnosis and monitoring of the disease are based on the clinical picture. To assess the disorders of other organs, additional tests need to be performed. Recently, the examination of blood morphology has been enriched with modern haematological parameters, i.e., Extended Inflammation Parameters (EIP), which include RE-LYMPH (activated lymphocytes), AS-LYMPH (antibody-producing B lymphocytes), and NEUT-RI and NEUT-GI (activated neutrophils). In the study, higher values of new haematological parameters were observed in individuals with psoriasis than in healthy controls. A higher EIP value was noted in the group of individuals with plaque psoriasis than in the group of individuals with psoriatic arthritis. Implementation of these parameters into routine laboratory analysis will likely make it possible to estimate the severity of the inflammation and improve its assessment.